1998
DOI: 10.1007/s002620050485
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of immune suppressive CD34 + cells from normal bone marrow by Lewis lung carcinoma tumors

Abstract: Progressive growth of metastatic Lewis lung carcinoma (LLC-LN7) tumors is associated with increased levels of bone-marrow-derived CD34+ cells having natural suppressor (NS) activity toward T cells. The present studies determined whether tumor-derived products are responsible for this induction of NS activity. Culturing normal bone marrow cells with LLC-LN7-conditioned medium (LLC-CM) or with recombinant granulocyte/macrophage-colony-stimulating factor (GM-CSF) resulted in the appearance of NS activity. The dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…30 Granulocyte macrophage-colony-stimulating factor (GM-CSF) secretion has correlated with the capacity of tumor metastases and the GM-CSF and IL-3 in conditioned medium from Lewis lung carcinoma may induce MDSCs from bone marrow culture. 31 The concentration of GM-CSF plays a critical role in the balancing Submitted April 23, 2007; accepted September 7, 2007. Prepublished online as Blood First Edition paper, September 20, 2007; DOI 10.1182 DOI 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Granulocyte macrophage-colony-stimulating factor (GM-CSF) secretion has correlated with the capacity of tumor metastases and the GM-CSF and IL-3 in conditioned medium from Lewis lung carcinoma may induce MDSCs from bone marrow culture. 31 The concentration of GM-CSF plays a critical role in the balancing Submitted April 23, 2007; accepted September 7, 2007. Prepublished online as Blood First Edition paper, September 20, 2007; DOI 10.1182 DOI 10.…”
Section: Introductionmentioning
confidence: 99%
“…30 Granulocyte macrophage-colony-stimulating factor (GM-CSF) secretion has correlated with the capacity of tumor metastases and the GM-CSF and IL-3 in conditioned medium from Lewis lung carcinoma may induce MDSCs from bone marrow culture. 31 The concentration of GM-CSF plays a critical role in the balancing act between immune suppression by MDSCs and immune activation by mature dendritic cells. 7 Additional evidence suggests that many cytokines, such as tumor necrosis factor ␣ (TNF-␣), GM-CSF, interferon ␥ (IFN-␥), IL-6, IL-4, VEGF, transforming growth factor ␤ (TGF-␤), IL-10, and Flt3 ligand are likely to be involved in the differentiation of myeloid progenitors present in blood, bone marrow, and spleen.…”
Section: Introductionmentioning
confidence: 99%
“…16,20,25 Our prior studies had shown the mobilization of CD34 1 progenitor cells into the peripheral blood of patients and animals whose tumors produce GM-CSF. 7,11,26 These include HNSCC and the murine LLC model. We had also previously shown the feasibility of using cytokine-containing implants for cell recruitment to the site of tumor excision.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Our studies have shown that these immune inhibitory CD34 1 cells are mobilized by tumor secretion of GM-CSF and that they are present in increased numbers in mice bearing Lewis lung carcinoma (LLC) tumors and in patients with head and neck squamous cell carcinomas. 7,11 They are also present within the cancer mass. Studies to determine the mechanisms that lead to their appearance within the tumor tissue showed that they can be chemoattracted by tumor-derived soluble products, with almost all of the chemotactic activity being attributable to VEGF.…”
mentioning
confidence: 99%
“…Earlier studies have described the presence of natural suppressors of lymphoproliferative responses with myeloid-cell characteristics in mice and humans (18)(19)(20)(21)(22). The finding that suppressive monocytes expressing CD11b/Mac-1 accumulate in the spleens of tumor-bearing mice (23), has led to the identification of T cell suppressors that express CD11b/Mac-1 and Gr-1 antigens in the spleens of mice immunized with highly immunogenic recombinant anti-cancer vaccines and tumor-bearing mice (24)(25)(26)(27) The fact that MDSC immune suppression can be reversed in vitro and in vivo has led to the development of a multitude of strategies in cancer therapy.…”
Section: Dedicationmentioning
confidence: 99%